2016
DOI: 10.1038/tp.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Association of thalamic hyperactivity with treatment-resistant depression and poor response in early treatment for major depression: a resting-state fMRI study using fractional amplitude of low-frequency fluctuations

Abstract: Despite novel antidepressant development, 10–30% of patients with major depressive disorder (MDD) have antidepressant treatment-resistant depression (TRD). Although new therapies are needed, lack of knowledge regarding the neural mechanisms underlying TRD hinders development of new therapeutic options. We aimed to identify brain regions in which spontaneous neural activity is not only altered in TRD but also associated with early treatment resistance in MDD. Sixteen patients with TRD, 16 patients with early-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 79 publications
6
57
0
Order By: Relevance
“…The predominant finding of this study was thalamo-temporal hyperconnectivity in MDD, which was also related to the severity of depression symptoms. This is in line with some other neuroimaging studies showing a positive relationship between thalamic activity and both symptoms (Milak et al, 2005) and treatment response (Yamamura et al, 2016) in MDD. However, we instead show that connectivity between thalamus and cortex is associated with severity of symptoms, and not just related to activity in thalamus, thus extending the implications of these previous studies into a network context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predominant finding of this study was thalamo-temporal hyperconnectivity in MDD, which was also related to the severity of depression symptoms. This is in line with some other neuroimaging studies showing a positive relationship between thalamic activity and both symptoms (Milak et al, 2005) and treatment response (Yamamura et al, 2016) in MDD. However, we instead show that connectivity between thalamus and cortex is associated with severity of symptoms, and not just related to activity in thalamus, thus extending the implications of these previous studies into a network context.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, some studies have also documented associations between thalamic activity and treatment outcomes. For example, patients with treatment resistant depression (TRD) had greater spontaneous thalamic activity compared to non-TRD patients (Yamamura et al, 2016). In this same study, a lower clinical improvement in response to antidepressants correlated with higher thalamic activity.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, the present study revealed the presence of thalamo-temporal hypo-connectivity in hemodialysis patients, which may be due to impaired thalamo-cortical modulation underlying emotional disturbances. This is in line with previous neuroimaging studies in major depressive disorders (Milak et al, 2005;Yamamura et al, 2016). Nevertheless, thalamo-cortical networks may be a potential candidate marker for psychopathology in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the ventral tegmental area is connected to the nucleus accumbens through the mesolimbic system, the classical dopaminergic pathway associated with schizophrenia, and functional data shows a decrease of connectivity between VTA and several brain regions, including the thalamus, in unmedicated schizophrenic patients (Hadley et al, 2014). The pathophysiology of others diseases, such as drug addiction, depression, temporal lobe epilepsy and attention deficit and hyperactivity disorder involve modifications in the nucleus accumbens, medial septal nuclei or the thalamic nuclei that connect limbic regions as well as dysfunctional connectivity of the DMN (Table 4; Butler et al, 2013;Dinkelacker et al, 2015;Ivanov et al, 2010;Scofield et al, 2016;Vialou et al, 2010;Voets et al, 2012;Volkow et al, 2011;Yamamura et al, 2016;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%